Microbiome analysis of gut bacterial communities of healthy and diseased Malaysian mahseer (Tor tambroides) using 16S rRNA metagenomics approach - Mei, Melinda Lin Lau; Jia, Cindy Yung Kho; Whye, Leonard Kit Lim; Siew, Chuiang Sia; Chung, Hung Hui; Samuel, Lihan; Kasing, Apun (Malaysian Society for Microbiology, 2022)
Aims: The gut microbiota is referred to as an ‘extra organ’ and is critical in assisting the host in terms of nutrition and immunity. Environmental stressors could alter the gut microbial community and cause gut inflammation. This study aimed to investigate and compare the gut microbiota community between healthy and diseased Tor tambroides. Methodology and results: In this study, such gut microbial alterations were explored using NGS-based 16S rDNA targeted sequencing on the Malaysian mahseer (T. tambroides). Three healthy adult and three diseased adult Malaysian mahseers (showing signs of exophthalmia, coelomic distension and petechial haemorrhage) were obtained from LTT Aquaculture Sdn Bhd. Our results revealed significant differences in microbial diversity, composition and function between both populations of T. tambroides. Alpha diversity analysis depicts lower diversity of gut microbiota composition in diseased T. tambroides as compared to the healthy group. In particular, Enterobacteriaceae, Aeromonas, Bacteroides, Vibrio and Pseudomonas were found within gut microbiota of the diseased fishes. In addition, cellulose degrading bacteria and protease-producing bacteria were identified from the gut of T. tambroides. Conclusion, significance and impact of study: Thus, our findings emphasized on the association between the alteration in gut microbiota composition and infectious abdominal dropsy (IAD) in T. tambroides. This finding is important to provide basic information for further diagnosis, prevention and treatment of intestinal diseases in fish.